2017
DOI: 10.5811/cpcem.2017.3.33348
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Rupture: A Tough Nut to Crack

Abstract: Blunt scrotal injury represents a diagnostic dilemma for emergency physicians (EP). Consequently, point-of-care ultrasound (POCUS) has emerged as a tool for early investigation of the acute scrotum in the emergency department. We describe a case where an EP used scrotal POCUS to immediately visualize the loss of testicular contour and underlying heterogeneous parenchyma to rapidly make the diagnosis of testicular rupture in a young male presenting with scrotal trauma. The use of POCUS in this case expedited th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The anatomical lay of the testes in combination with the increasing use of protective cups has made this an increasingly uncommon event. 1 The right testis is more commonly injured due to its position and propensity in being trapped against the pubic bone. Previous studies have revealed that about 50 kg of force is required to rupture a testis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anatomical lay of the testes in combination with the increasing use of protective cups has made this an increasingly uncommon event. 1 The right testis is more commonly injured due to its position and propensity in being trapped against the pubic bone. Previous studies have revealed that about 50 kg of force is required to rupture a testis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that about 50 kg of force is required to rupture a testis. 1 , 2 The clinical examination of the traumatized scrotum can be challenging due to the pain and swelling with misdiagnosis often common. Due to misdiagnoses, there has been an increased rate of traumatic sequelae to include: orchiectomy, atrophy, and infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported rates of testicular injury with sports participation may underestimate the prevalence of these injuries among adolescent and young adult athletes among whom testicular protective equipment is infrequently used. Any kind of contact sport, without the use of protective aids, may be associated with genital trauma [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Point-of-care ultrasound (POCUS) has increasingly been used for early investigation of the acute scrotum [4]. However, the literature is limited to case reports, and two retrospective studies [1,4,5,9,11]. Using a high frequency linear array probe, the testes should be individually visualized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation